Agomelatine's antiglycoxidative action—In vitro and in silico research and systematic literature review - Nesterowicz, Miłosz; Lauko, Kamil Klaudiusz; Żendzian-Piotrowska, Małgorzata; Ładny, Jerzy Robert; Zalewska, Anna; Maciejczyk, Mateusz (Frontiers in Psychiatry, 2023)
Introduction Agomelatine is an atypical antidepressant drug enhancing norepinephrine and dopamine liberation; nevertheless, additional mechanisms are considered for the drug's pharmacological action. Since protein glycoxidation plays a crucial role in depression pathogenesis, agomelatine's impact on carbonyl/oxidative stress was the research purpose. Methods Reactive oxygen species scavenging (hydroxyl radical, hydrogen peroxide, and nitrogen oxide) and antioxidant capacity (2,2-diphenyl-1-picrylhydrazyl radical and ferrous ion chelating assays) of agomelatine were marked. Agomelatine's antiglycoxidation properties were assayed in sugars (glucose, fructose, and galactose) and aldehydes- (glyoxal and methylglyoxal) glycated bovine serum albumin (BSA). Aminoguanidine and α-lipoic acid were used as standard glycation/oxidation inhibitors. Results Agomelatine did not show meaningful scavenging/antioxidant capacity vs. standards. Sugars/aldehydes increased glycation (↑kynurenine, ↑N-formylkynurenine, ↑dityrosine, ↑advanced glycation end products, and ↑β-amyloid) and oxidation (↑protein carbonyls and ↑advanced oxidation protein products) parameters in addition to BSA. Standards restored BSA baselines of glycation and oxidation markers, unlike agomelatine which sometimes even intensifies glycation above BSA + glycators levels. Molecular docking analysis of agomelatine in BSA demonstrated its very weak binding affinity. Discussion Agomelatine's very low affinity to the BSA could proclaim non-specific bonding and simplify attachment of glycation factors. Thereby, the drug may stimulate brain adaptation to carbonyl/oxidative stress as the systematic review indicates. Moreover, the drug's active metabolites could exert an antiglycoxidative effect.